Spray cooling of electric motor coil windings. (June 2016) - Guechi, MR; Desevaux, P; Baucour, P; Espanet, C; Brunel, R; Poirot, M
The spraying of an impinging jet is an effective way to cool heated surfaces. A numerical model has been previously developed to predict the heat transfer with phase change between a hot plate surface and a two-phase impinging jet. This Computational Fluid Dynamics (CFD) model is applied here for studying the spray cooling of conventional and impregnated coil windings of electric motors. The numerical results are compared with measurements obtained on an experimental test bench. The confrontation numerical/experimental is carried out by comparing the distribution of temperature inside the coil windings. This study has confirmed the interest of the cooling spray technique. The interest to fill coil windings with impregnating resin of good thermal conductivity is less obvious. When using spray cooling, the lowest temperatures are reached within conventional coil windings.